Uniqueness of stationary equilibrium payoffs in coalitional bargaining - Hülya Eraslan; Andrew McLennan (The Johns Hopkins University, Department of Economics, 2010)
We study a model of sequential bargaining in which, in each period before an agreement is reached, the proposer's identity (and whether there is a proposer) are randomly determined; the proposer suggests a division of a pie of size one; each other agent either approves or rejects the proposal; and the proposal is implemented if the set of approving agents is a winning coalition for the proposer. The theory of the fixed point index is used to show that stationary equilibrium expected payoffs of this coalitional bargaining game are unique. This generalizes Eraslan (2002) insofar as: (a) there are no restrictions on the structure of sets of winning coalitions; (b) different proposers may have different sets of winning coalitions; (c) there may be a positive probability that no proposer is selected.
Keywords: 330; Noncooperative bargaining; multilateral bargaining; TU games; simple games; coalitions; legislative bargaining; fixed points; fixed point index